2016
DOI: 10.1007/s11916-016-0593-5
|View full text |Cite
|
Sign up to set email alerts
|

Carotid and Vertebral Dissection Imaging

Abstract: Carotid or vertebral artery dissection is the result of a tear in the vessel lining wherein the intima separates the media. This creates a false or pseudo lumen, often accompanied by hemorrhage into the arterial wall. Dissection of these craniocervical vessels often manifests with pain alone but, if untreated, may result in severe neurologic compromise. The causes of dissection are multifactorial, including spontaneous, iatrogenic, and traumatic insults. Regardless of etiology, treatment consists primarily of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…18 IMH, which can be identi ed on MSDE, characteristically has a crescentic shape adjacent to the vessel lumen and often spirals along the length of the artery. 18,19,20 Previous reports suggested that the MSDE-3D-TSE sequence was useful for assessing vessel walls in the dissection and aneurysms. [21][22][23] MSDE causes phase dispersion of blood spin using a magnetic eld to suppress blood ow signal, producing 3D T1-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…18 IMH, which can be identi ed on MSDE, characteristically has a crescentic shape adjacent to the vessel lumen and often spirals along the length of the artery. 18,19,20 Previous reports suggested that the MSDE-3D-TSE sequence was useful for assessing vessel walls in the dissection and aneurysms. [21][22][23] MSDE causes phase dispersion of blood spin using a magnetic eld to suppress blood ow signal, producing 3D T1-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of intramural hematoma (IMH) is the basis of the diagnosis of CAD [18]. IMH, which can be identified on MSDE, characteristically has a crescentic shape adjacent to the vessel lumen and often spirals along the length of the artery [18,19,20]. Previous reports suggested that the MSDE-3D-TSE sequence was useful for assessing vessel walls in the dissection and aneurysms [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…DSA is gradually being replaced by noninvasive imaging methods. [ 10 ] Concerning intramural hematoma, cross-sectional images of MRI have shown an advantage. Cristina et al [ 11 ] believe that MRI is the only reliable method for exploring the arterial wall.…”
Section: Discussionmentioning
confidence: 99%